МЕТОДИЧНІ УМОВИ ОРГАНІЗАЦІЇ ПРАКТИЧНИХ ЗАНЯТЬ З ДИСЦИПЛІНИ «ТЕОРІЯ ЙМОВІРНОСТЕЙ ТА МАТЕМАТИЧНА СТАТИСТИКА» ДЛЯ СТУДЕНТІВ ЕКОНОМІЧНИХ СПЕЦІАЛЬНОСТЕЙ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2013)
The article presents methodical requirements to the organization of practical classes in the discipline «Theory ofprobability and statistics in maths». The role of economy based tasks in the process of building students' skills andabilities necessary for their future professional activity is defined.